Meat batter production in an extended vane pump–grinder injecting curing salt solutions to reduce energy requirements: variation of curing salt amount injected with the solution. (1st April 2016) - Irmscher, Stefan B; Terjung, Eva‐Maria; Gibis, Monika; Herrmann, Kurt; Kohlus, Reinhard; Weiss, Jochen
Abstract: BACKGROUND: The integration of a nozzle in an extended vane pump–grinder system may enable the continuous injection of curing salt solutions during meat batter production. The purpose of this work was to examine the influence of the curing salt amount injected with the solution (0–100%) on protein solubilisation, water‐binding, structure, colour and texture of emulsion‐type sausages. RESULTS: The amount of myofibrillar protein solubilised during homogenisation varied slightly from 33 to 36 g kg −1 . Reddening was not noticeably impacted by the later addition of nitrite. L * ranged from 66.9 ± 0.3 to 67.8 ± 0.3, a * from 10.9 ± 0.1 to 11.2 ± 0.1 and b * from 7.7 ± 0.1 to 8.0 ± 0.1. Although softer sausages were produced when only water was injected, firmness increased with increasing curing salt amount injected and was similar to the control when the full amount of salt was used. The substitution of two‐thirds of ice with a liquid brine may enable energy savings due to reduced power consumptions of the extended vane pump–grinder system by up to 23%. CONCLUSION: The injection of curing salt solutions is feasible without affecting structure and colour negatively. This constitutes a first step towards of an 'ice‐free' meat batter production allowing for substantial energy savings due to lower comminution work. © 2016 Society of Chemical Industry